The Role of Nitric Oxide Metabolites in the Formation of Endothelial Dysfunction in Children with Persistent Bronchial Asthma - Yu.V. Odinets; Y.V. Vasilchenko (Zaslavsky O.Yu., 2016)
The aim of the study was to assess the role of nitric oxide metabolites in the development of endothelium dysfunction in children with persistent bronchial asthma in acute period and during remission Material and methods. Fifty eight children aged 6-17 years old suffering from persistent bronchial asthma in the period of exacerbation and remission of disease and 15 healthy children of control group have been examined in order to evaluate the role of the metabolites of nitric oxide levels for the development of endothelium dysfunction in the children with persistent bronchial asthma. There were determined serum blood S-nitrosothiol, NO2, NO3, the intima-media complex by the ultrasound duplex scanning and endothelium-dependent dilation status of the brachial artery by cuff probe. Results. It showed a reduction in the levels of nitric oxide metabolites and endothelium-dependent dilation of the brachial artery, intima-media thickening in the period of exacerbation. There was revealed a significant increase in the levels of nitric oxide metabolites and endothelium-dependent dilation of the brachial artery compared with the period of exacerbation, but these findings are still lower in comparison with the control group, which indicates the presence of persistent changes in the vascular wall. Conclusion. The nitric oxide metabolites as well as the carotid intimal medial thickness and endothelium-dependent dilation of brachial artery should be marders of endothelium dysfunction in the children with bronchial asthma.